(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Today, the planet Earth is confronting the ecological crisis which has been generally acknowledged by scientists, politicians, environmentalists and academicians around the world. Data about these difficulties has been across the board for a very long while now, yet next to no has been done to address them decidedly. Be that as it may, the extent that abstract field is worried, there is boundless mindfulness towards ecological concerns through the ongoing scholarly hypotheses like Ecocriticism. Nature and Literature have constantly shared a cozy relationship, as it is prove underway of writing. Writing is notable for reflecting contemporary issues and it is this feeling of concern and its refection in writing that has offered ascend to another part of scholarly hypothesis, specifically Ecocriticism. This paper displays a blueprint of ecocriticism, trailed by an Ecocritical investigation of Ruskin Bond’s